2013
DOI: 10.1371/journal.pone.0058595
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Change in CD4 Lymphocyte Count and Weight among HIV Infected Patients on Anti-Retroviral Treatment in Ethiopia: A Retrospective Longitudinal Study

Abstract: BackgroundAntiretroviral treatment (ART) has been introduced in Ethiopia a decade ago and continues to be scaled up. However, there is dearth of literature on the impact of ART on changes in CD4 lymphocyte count and weight among patients on treatment.ObjectiveTo determine the predictors of change in CD4 lymphocyte count and weight among HIV/AIDS infected patients taking antiretroviral treatment in eastern Ethiopia.MethodsA retrospective cohort study was conducted among HIV/AIDS patients taking ART from 2005 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
28
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 21 publications
24
28
4
Order By: Relevance
“…This study was in agreement with the studies of Reda et al (2013) and that of Adams and Luguterah (2013), in showing the benefit of early treatment. A higher baseline CD4 cell count would result in a better rate of recovery of patients on ART.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 93%
See 3 more Smart Citations
“…This study was in agreement with the studies of Reda et al (2013) and that of Adams and Luguterah (2013), in showing the benefit of early treatment. A higher baseline CD4 cell count would result in a better rate of recovery of patients on ART.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 93%
“…This study showed (for the Age≥15 years dataset) that the age of patients did not have any significant effect on the evolution in contrast to the studies of Adams and Luguterah (2013) and that of Reda et al (2013). This could be explained by the relatively young nature of the patients considered with median age (IQR) = 34 (28-40).…”
Section: Discussion and Concluding Remarkscontrasting
confidence: 74%
See 2 more Smart Citations
“…The decision to initiate ART in adults and adolescents relies on clinical and immunological assessment [5], WHO emphasizes the importance of using clinical parameters in deciding when to initiate ART, however it is recognized that the value of clinical staging in decision making of when to initiate and monitor ART is improved by additional information provided by baseline and subsequent (longitudinal) CD4 + T-lymphocyte cell count. CD4 + cell count criteria for ART initiation in adults and adolescents for low and middle-income countries according to WHO 2013 guidelines of 200 -350 cells/mm 3 is used and <200 cells/mm 3 are also initiated on ART.…”
Section: Introductionmentioning
confidence: 99%